Inclusion and equity, vectors of communication for all (Cadernos de Sociomuseologia, 2024)
This article is based on the premises of the functional diversity model, which entails mutual respect and a collective effort to reduce the gap between what is offered and demanded and what each person is capable of doing in a given context. One of the most important needs of human beings is their relationship with others. Communication is essential for expressing needs, desires, exchanging viewpoints, increasing mutual understanding, making friends, and achieving professional fulfillment.Thus, it is almost a duty for us to make every effort, using all available means, to enable those among us with communication difficulties to express themselves and be understood by those around them. Augmentative and alternative communication, combined with technology, aims to provide methods that enhance remaining communication abilities or offer substitutes in cases where there is an absence of any perceivable form of communicative expressionKeywords: Inclusion; accessible communication, equity